IMPLEMENTASI PROGRAM RAIL CLINIC SEBAGAI WUJUD TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PT KERETA API INDONESIA: Implementation Of The Rail Clinic Program As A Form Of Social And Environmental Responsibility By Pt Kereta Api Indonesia - Muhammad Eka Anugra; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2026)
The Rail Clinic Program is an implementation of Corporate Social Responsibility (CSR) by PT Kereta Api Indonesia (Persero), which aims to provide free health services to communities living around railway lines. The issue is how to organize the Rail Clinic program as a form of CSR implementation by state-owned enterprises in the railway sector in Indonesia. The research method used is a normative, descriptive type of research with a legal approach, using primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results and conclusion of the analysis of the implementation of the Rail Clinic Program are based on PT. KAI's internal regulations as outlined in the SOP with reference to Article 87 E of Law Number 1 of 2025, as well as sectoral regulations in the field of railways. This program has been implemented effectively by involving community participation and providing direct benefits for improving the welfare of communities around the railroad tracks, although health services are still incomplete and not supported by comprehensive health facilities. As a suggestion, the Rail Clinic Program should be optimized to provide better health services to the community.